SINGKUH: WHERE HUMAN IMAGINATION MEETS TECHNOLOGICAL SOUND EXPERIMENTATION - Putri, Ni Made Ayu Dwara; Rafa, Damay Nouvanala Radja (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
“Singkuh” is an experimental music composition based on the Balinese concept of "singkuh," meaning "strange." The work challenges traditional musical conventions by introducing unconventional sounds, techniques, and forms, contributing to the field of experimental music. To explore innovative approaches to music-making, breaking traditional norms, and expanding the possibilities of sound exploration through unconventional techniques and instruments. The composition utilizes VCV Rack software to operate modular synthesizers, providing effects for acoustic instruments. The creation process follows the Art Consortium's five stages: preparation, elaboration, synthesis, concept realization, and evaluation. The result is a 30-minute experimental composition for acoustic and electronic instruments. It includes diverse instruments such as piano, synthesizers, ocarina, kalimba, harmonica, bird whistles, and more. The work is divided into five sections emphasizing different experimental aspects. “Singkuh” introduces innovative techniques, instruments, and notations to experimental music. It expands musical boundaries and encourages both musicians and listeners to explore diverse sound possibilities.